2018
DOI: 10.14423/smj.0000000000000777
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Emergence in Pediatric Patients with Neurologic Disease Presenting for Ambulatory Surgery

Abstract: In this case-controlled retrospective study, there was a prolongation of anesthetic emergence and hospital discharge times for pediatric patients with severe neurologic disease, mostly independent of external factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…studies had showed the incidence rate of DEA was between 8.1% to 50.5% [4,5]. Anesthetic drugs usages, improper management or practice during anesthesia, surgical factors [6] and patient's individual variation [7,8] are risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…studies had showed the incidence rate of DEA was between 8.1% to 50.5% [4,5]. Anesthetic drugs usages, improper management or practice during anesthesia, surgical factors [6] and patient's individual variation [7,8] are risk factors.…”
Section: Introductionmentioning
confidence: 99%